Perancangan Desain Kemasan Minuman Teh Untuk Meningkatkan Brand Awareness - Renzy Ayu Rohmatillah; Nabila Rahmi Oktaviani; Diana Setia Dewi (LPPM STIKI Malang, 2025)
Packaging has various functions such as protecting products from various causes of damage, as a medium for product communication and branding to consumers, maintaining products so that they last longer, and triggering consumer buying interest. The appearance of the packaging is one of the elements that can build brand identity and attract consumer attention. MSMEs